Hydrothermal Synthesize of HF-Free MIL-100(Fe) for Isoniazid-Drug Delivery - Simon, Meta A. (Sci Rep, 2019)
Sustainable development of drug delivery materials with good biocompatibility and controlled-release is a popular topic among researchers. In this research study, we demonstrated the potential of the metal-organic framework, that is MIL-100(Fe), as a drug delivery platform for isoniazid (INH). The MIL-100(Fe) was prepared by using the hydrofluoric acid-free hydrothermal method. Several physical measurements were conducted to characterize the MIL-100(Fe), including x-ray diffraction (XRD), scanning electron microscopy (SEM), nitrogen sorption, and thermal-gravimetric (TG). The synthesized MIL-100(Fe) has octahedron-shaped particles with superior properties, that is large surface area (1456.10 m(2)/g) and pore volume (1.25 cm(3)/g). The drug loading rate and capacity were determined by means of adsorption kinetic and isotherm. The studied INH@MIL-100(Fe) adsorption system kinetics follow the pseudo-first-order model, while the isotherm system follows the Langmuir model with the maximum adsorption capacity of 128.5 mg/g at 30 °C. MIL-100(Fe) shows adequate biocompatibility, also exhibits a reasonable and controlled drug release kinetics. The results obtained show that MIL-100 (Fe) can be a good choice of drug delivery platform among other available platforms.